سمـات التوجيه النحوي عند الزمخشري في تفسيره المعروف بالكشاف - أحمد، محمد سعد محمد (جامعة الخرطوم - كلية التربية, 2015)
This study aims to explore parsing grammar as has been studied by the Arab linguist scholar (Al-zamakhsharee) in his book (Alkashaaf), trying to review his grammatical insights in relation to other Arab grammarians concepts. This hopefully will discover the major differences between those grammarians' concepts and Al-zamakhsharee besides identifying his principal unique contributions in this regard as well as examining the impacts of (Almoutazeela) doctrine of philosophy in all works. It is clearly evident from the reviewed literature in this study that the Arab linguist (Alzamakhshari) grammar analysis approach is basically built on the former grammarians opinions, and user adds to them his own contributions and refinement. For instance, we can recognize that he may sometimes agree with Al –bsreen with Al koofi'een; in other instances. Furthermore, he may also agree with the concepts of other Arab scholars. His grammatical option may often be unique in some of his grammatical works.
تهدف هذه الدراسة إلى الوقوف عند التخريج النحوي عند العلّامة الزمخشري في تفسيره الكشاف محاولة استعراض آرائه النحوية فيه وموازنة ومقارنة لها بآراء الآخرين من النحاة والمُعربين؛ ممّا قد يتيح فرصة النظر في موافقته لبعضهم ومخالفته لآخرين ومساندته لمذهب نحاة بعينهم، وكشف انفراداته النحوية عن الجميع، وتأثير النزعة الاعتزاليّة عنده في ذلك كلّه. ويمكن للناظر في الصفحات القادمات أن يلحظ أن الزمخشري في كشّافه كان يبني توجيهه النحوي على أسس السابقين ثم يُضيف إليها بشخصيته الفذّة وجودة قريحته وما أتيح له من غزارة علم ما يراه مناسبا، فقد نجده يوافق البصريين أحيانا، كما نراه يأخذ بمذهب الكوفيين في مرات أُخرى، وقد يوافق مذاهب بعض النحويين المنفردة، ويمكن أن يأتي رأيه النحوي متفرّدا وحيدا في بعض التخريجات النحوية.
Keywords: الزمخشري، محمود بن عمر بن محمد بن عمر الخوارزمي، ت. 538 هـ. -- النحو العربى -- اللغة العربية -- تفسير القران -- كتاب " الكشاف "